Role of the R349 Gene and Its Repeats in the MIMIVIRE Defense System - Mougari, Said; Abrahao, Jonatas; Oliveira, Graziele P.; Bou Khalil, Jacques Y.; La Scola, Bernard (Frontiers in Microbiology, 2019)
MIMIVIRE is a defense system described in lineage A Mimivirus (Mimiviridae family) that mediates resistance against Zamilon virophage. It is composed of putative helicase and nuclease associated with a gene of unknown function called R349, which contains four 15 bp repeats homologous to the virophage sequence. In a previous study, the silencing of such genes restored virophage susceptibility. Moreover, the CRISPR Cas-4 like activity of the nuclease has recently been characterized. In this study, a recently isolated Mimivirus of lineage A with R349 gene lacking 3 of 4 repeats was demonstrated to be susceptible to Zamilon. To reinforce the importance of the R349 gene in the MIMIVIRE system, we developed and presented, for the first time to our knowledge, a protocol for Mimivirus genomic editing. By knocking out R349 gene in a Mimivirus lineage A, we observed the replication of Zamilon, indicating that this gene is critical in the resistance against this specific group of virophages.